Avaliação dos efeitos da infecção com diferentes cepas de Trypanosoma cruzi em características fenotípicas e funcionais de monócitos e linfócitos humanos - Luisa Mourao Dias Magalhaes (2013)
According to the World Health Organization, there are about 10 million people infected with Trypanosoma cruzi worldwide, mostly in Latin America, and more than 25 million people at risk of infection. T. cruzi is currently classified into six DTUs, called Tc I to VI according Zingales (2009). Our hypothesis is that different strains infect human monocytes differently, causing diferent immune changes in these cells and lymphocytes. Thus, the project assessed the infectivity of clone Colombiana 1.7 and the Y strain belonging respectively to groups T. cruzi I and II, and the immunological profile induced by them in the host cell. To perform the analyzsis, parasite strains were grown in VERO cells in incubators at 37 ° C and 5% CO2. Trypomastigote forms of the parasites were stained with CFSE and used in infection of peripheral blood cells from healthy donors for 3 and 72 hours. After this period, the red cells were lysed and the cells incubated with monoclonal antibody directed against activation markers, co-stimulatory and cytotoxicity molecules, and cytokines (anti-CD14, CD16, CD4, CD8, TLR2, TLR4, CD80, CD86, HLA- DR, CD28, CTLA-4, CD69, IL-12, IL-10, IL-17, TNFa, IFNg and granzyme A). Data were obtained by flow cytometry and analysis performed using the Flow-Jo software. Our results demonstrate that, despite no difference in the frequency of CFSE+ CD14+ cells when infection was performed by Y strain or clone Colombiana 1.7, differences were observed in the activation of monocytes after infection by different strains. When infection was carried out by Y strain, we observed higher activation of CD16- subpopulation of monocytes, whereas when infection was carried out by clone Colombiana 1.7, the CD16+ subpopulation was the most activated. It was also observed a reduced expression of IL-10 by CFSE+ monocytes after infection with strain Y compared to infection with clone Colombiana 1.7. Finally, it was possible to observe a more inflammatory environment after infection with strain Y than after infection Colombiana 1.7, by studying the ratio of the cytokines TNFa and IL-10. There was also a reduction of the expression of CTLA-4 in CD8+ T cells after 72 hours of infection by the two strains. In summary, our results showed that infection with different strains of T. cruzi leads to functional and phenotypic changes in human monocytes and lymphocytes. These findings are important because they provide information relevant to the understanding of the immune response triggered by different T. cruzi strains, which could aid in understanding the disease and open perspectives for new control methods.